Endocrine Mucin-Producing Sweat Gland Carcinoma of the Eyelid Associated With Mucinous Adenocarcinoma. Issue 2 (March 2018) - Charles, Norman C.; Proia, Alan D.; Lo, Christopher
Abstract : Endocrine mucin-producing sweat gland carcinoma, a rare, low-grade neoplasm with predilection for the eyelids, has been posited as a precursor to invasive mucinous adenocarcinoma. Endocrine mucin-producing sweat gland carcinoma and its concurrence with mucinous adenocarcinoma have received little attention in the ophthalmic literature. The combination of the 2 histologic patterns parallels endocrine ductal carcinoma in situ of the breast and its transition to Type B invasive mucinous carcinoma. The authors describe a 59-year-old man who developed a tumor of the right upper eyelid showing endocrine mucin-producing sweat gland carcinoma in the outer dermis and extensive mucinous carcinoma in the deeper tissue. Immunohistochemical analysis showed positivity for endocrine markers chromogranin, synaptophysin, CD56, estrogen, and progesterone in each histologic component of the tumor. This research was conducted in conformity with the Helsinki Declaration and HIPPA regulations. Abstract : A rare eyelid tumor in a 59-year-old man demonstrated a concurrence of endocrine mucin-producing sweat gland carcinoma and invasive mucinous adenocarcinoma.